Optimization of automotive components using the variational technology - Cardoso, Valdir Mendes; Silva, Emílio Carlos Nelli (SAE International, 2004)
In a traditional finite element analysis, any change in the parameters that define the geometry or the physic properties requires a new analysis run in order to check the component performance. This can be a limitation in the ability of Engineers to conduct a what-if study, mainly when several input variables can be changed, that would require a large number of analyses, since the number is an exponential function in terms of variables. This work tries to explain what the Variational Technology is and how this is used to find an optimized automotive component design. The theory of this methodology is shown and some example where it has been applied is discussed. This Technology helps the Engineer during the design phase by using a series expansion that generate a response surface, where the Engineer can easily find the best design for each objective. The results are calculated in a single analysis using very accurate approximation functions. Since this approach takes just a little bit more time than a traditional analysis for one set of parameters. Then, the Engineer can quickly verify a large number of design alternatives using a small fraction of the time that would be required to run several analyses for the each individual set of variables. In a competitive market where the time of development of a new product can define if it will be successful or not, the time of project is a very important variable and to reduce it was the mainly objective of this work. The paper intends to show that with some mathematical tools it's possible to find the optimal design parameters without increasing significantly the Engineering work. Copyright © 2004 Society of Automotive Engineers, Inc.